Symptoms of Residential Exposure to Insecticides and Associated Factors Among Young Thai Children in Urban Areas - Pongtipat Chaiyamong; Titaporn Luangwilai; Parichat Ong-Artborirak (Children)
Background/Objectives: Household insecticide use may impact the health of young children in urban communities, but little is known about its acute effects. This cross-sectional study aimed to investigate the symptoms that may have been related to residential insecticide exposure and its associated factors in young children in urban areas. Methods: The study included 375 primary caregivers of children aged 6 months to 5 years from the Bangkok Metropolitan Region, Thailand, who had used insecticides in their homes within the past 6 months. An interviewer-administered questionnaire collected data on caregiver and child demographics, household insecticide use and exposure, child behaviors, and the history of child symptoms following insecticide use. Results: The findings revealed that 9.6% of young children had experienced symptoms at some point during or after household insecticide use, with coughing (66.7%), skin rash/irritation (44.4%), and runny nose (25.0%) being the most common. The final logistic regression model using backward selection indicated that factors statistically significantly associated with symptoms included being a male child (OR = 3.38; 95% CI = 1.48–7.71), hand/object-to-mouth behaviors (OR = 2.69; 95% CI = 1.26–5.74), weekly use of insecticides (OR = 2.77; 95% CI = 1.22–6.26), use of insecticide chalk (OR = 3.64; 95% CI = 1.32–10.08), and use of mosquito repellent spray/lotion (OR = 2.51; 95% CI = 1.13–5.61). Additionally, the use of insecticide spray (OR = 2.72; 95% CI = 0.97–7.65), opening doors/windows for ventilation (OR = 0.46; 95% CI = 0.21–1.02), and consistently cleaning floors with a wet cloth after use (OR = 0.52; 95% CI = 0.24–1.11) were marginally associated. Conclusions: Residential exposure to household insecticides can lead to acute health effects, primarily respiratory symptoms, in young children in urban communities. Caregivers should be informed of these health risks to reduce children’s exposure.